The mechanical property and corrosion resistance of Mg-Zn-Nd alloy fine wires in vitro and in vivo - Ming Gao; Di Na; Xiangqiao Ni; Lihui Song; Iniobong P. Etim; Ke Yang; Lili Tan; Zheng Ma (Bioactive Materials, 2021)
Titanium and its alloy are commonly used as surgical staples in the reconstruction of intestinal tract and stomach, however they cannot be absorbed in human body, which may cause a series of complications to influence further diagnosis. Magnesium and its alloy have great potential as surgical staples, because they can be degraded in human body and have good mechanical properties and biocompatibility. In this study, Mg-2Zn-0.5Nd (ZN20) alloy fine wires showed great potential as surgical staples. The ultimate tensile strength and elongation of ZN20 alloy fine wires were 248 MPa and 13%, respectively, which could be benefit for the deformation of the surgical staples from U-shape to B-shape. The bursting pressure of the wire was about 40 kPa, implying that it can supply sufficient mechanical support after anastomosis. Biochemical test and histological analysis illustrated good biocompatibility and biological safety of ZN20 alloy fine wire. The residual tensile stress formed on the outside of ZN20 fine wire during drawing would accelerate the corrosion. The second phase had a negative influence on corrosion property due to galvanic corrosion. The corrosion rate in vitro was faster than that in vivo due to the capsule formed on the surface of ZN20 alloy fine wire.